Protecting zakat and waqaf assets through takaful - Mohd Fauzi, Puteri Nur Farah Naadia; Abdul Rashid, Khairuddin; Hasan, Sharina Farihah; Ahmad Sarkawi, Azila; Aripin, Srazali (Sultan Agung Islamic University (UNISSULA), 2015)
In Islam, the fundamental instruments to safeguard welfare of Muslims are zakat and waqaf. Zakat and waqaf instruments to facilitate helping needy Muslims that would be inevitably involve management and assets i.e. money, land as well as properties. In the current economy climate, these assets; if are not manage properly could expose to variety of risks. Such risks require protections and conventionally, such protections are provided under variety of insurance schemes. In the Shariah, the protections of risks are allowed through the concept of takaful. This paper aims to discuss the activities of zakat and waqaf that may face risks and should consider to apply protection through takaful. Consequently, there is an opportunity for zakat-waqaf-takaful to collaborate. The study involves i) desk research and ii) discussions with experts in the field of fiqh mua’malat and procurement. The outcome of the study is to generate the idea on the possibility of two fundamental instruments, i.e. zakat and waqaf with takaful to collaborate. Discussions on the collaboration are herein proposed in the paper.